2007
DOI: 10.1007/s11274-007-9523-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimized conditions for the synthesis of vanillic acid under hypersaline conditions by Halomonas elongata DSM 2581T resting cells

Abstract: During growth on ferulic acid, Halomonas elongata DSM 2581 T was capable of promoting the formation of a significant amount of vanillic acid. The products were confirmed by high-performance liquid chromatography and gas chromatography mass-spectrometry analyses. To enhance the formation of vanillic acid and prevent its degradation, a resting-cell method using Halomonas elongata was developed. The growth state of the culture utilized for biomass production, the concentration of the biomass, the amount of feruli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…In the first method, fed batch, the cells were harvested in modified SM (1 g/L yeast extract was added as a sole carbon source) and ferulic acid was added when the cells were at the end of the exponential phase. In the second method, resting cell technique (Abdelkafi et al 2008), the cells in mineral medium supplemented with 1 g/L of yeast extract were harvested at the end of the exponential phase by centrifugation, after which cells were washed and suspended in saline/phosphate buffer and then incubated aerobically, at 33°C, in the presence of FA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first method, fed batch, the cells were harvested in modified SM (1 g/L yeast extract was added as a sole carbon source) and ferulic acid was added when the cells were at the end of the exponential phase. In the second method, resting cell technique (Abdelkafi et al 2008), the cells in mineral medium supplemented with 1 g/L of yeast extract were harvested at the end of the exponential phase by centrifugation, after which cells were washed and suspended in saline/phosphate buffer and then incubated aerobically, at 33°C, in the presence of FA.…”
Section: Methodsmentioning
confidence: 99%
“…Overhage et al (1999) and Calisti et al (2008) found that ferulic acid is first activated to feruloyl-CoA by a feruloyl-CoA synthetase and then the CoA thioester is subsequently hydrated and cleaved to vanillin and acetylCoA by an enoyl-CoA hydratase/aldolase. Abdelkafi et al (2006Abdelkafi et al ( , 2008 using Halomonas elognata strains found that the ferulic acid was rapidly transformed to vanillic acid at a high yield (80 %). In these studies (Abdelkafi et al 2006(Abdelkafi et al , 2008 however, no vanillin was produced which has a considerably higher value added product than vanillic acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the possibility of improving vanillin production from isoeugenol via inhibition of its further degradation and the prevention of biomass duplication by using resting cells strategy has been investigated. Many researchers have successfully explored this strategy for improvement of bioconversion processes [31][32][33]. Maximum vanillin yield (up to 141.45 mg L −1 , molar yield 16.4%) was obtained with this method (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial transformations of ferulic acid to a wide variety of aromatic compounds have been reported [7][8][9][10][11][12]. According to Priefert et al [12], the four major pathways of ferulic acid degradation with respect to the initial reaction are (1) nonoxidative decarboxylation, (2) side chain reduction, (3) coenzyme-A-independent deacetylation and (4) coenzyme-Adependent deacetylation.…”
Section: Introductionmentioning
confidence: 99%